Zika Virus-Associated Respiratory Tract Infection: A Rare Clinical Scenario (Pulse, 2025)
Introduction: The Zika virus, a flavivirus carried by arthropods, is mainly linked to febrile disease, rash, and neurological problems. Respiratory involvement, particularly hypoxemic respiratory failure with pneumonitis, is a rare presentation of Zika virus infection. Case Presentation: We describe a 70-year-old male Bangladeshi patient who had a history of hypertension presented with 10-day history of low-grade fever, myalgia, joint pain, and generalised weakness. Initial investigations, including complete blood count, blood cultures, and Dengue IgM antibody, were unremarkable. However, Zika virus RNA was detected via reverse transcriptase polymerase chain reaction (RT-PCR) from a blood sample. But the patient developed shortness of breath and chest pain on second day of hospitalization, later he was sent to the critical care unit after developing hypoxemia. Imaging showed a right-sided basal consolidation and a small pleural effusion, both of which are indicative of pneumonitis. Sputum culture and respiratory panel RT-PCR were negative for bacterial and viral pathogens. He was managed with high-flow nasal oxygen and intravenous antibiotics, resulting in significant clinical improvement. Conclusion: While pulmonary manifestations are well-documented in flaviviruses like dengue, Zika virus-induced pneumonitis is rare with few case mentioned in the literature. Particularly in endemic areas, clinicians should keep a close eye out for Zika virus infections in febrile diseases with unusual respiratory presentations.Pulse Volume 16, Issue 2 2024: 47-50